PERUBAHAN KUALITAS PELAYANAN PUBLIK & KEPUASAN PENGGUNA JASA KERETA API DI KOTA TASIKMALAYA - Ari . Ramdani (UNIVERSITAS ISLAM SYEKH YUSUF, 2020)
This research begins with some positive changes in the quality of public services that occur at PT. Indonesian Railways which turned out to have a positive impact on the level of satisfaction of users of railroad services, especially in the City of Tasikmalaya. Of course, this change is a factor that is the cause. So in this study questioned: how changes in the quality of public services, Factors that support the process of realizing the change in the quality of public services, and how satisfaction of train service users in the City of Tasikmalaya. To answer these questions and get information, qualitative research methods are used with interview techniques, documentation studies, and observations. The conclusion from the study was obtained that changes in the quality of public services that occurred so far PT. Indonesian Railways is indeed influenced by several factors, all of which are internal factors of PT. Indonesian Railways. And these changes prove that changes in the quality of public services have an impact on the level of public satisfaction. With the high level of satisfaction of users of railroad services, of course, this must be maintained by PT. Indonesian Railways. So that PT. Indonesian Railways will continue to be a trusted provider by land transportation users. Keywords: Quality of Public Services; Service User Satisfaction